Karakteristik Fisik dan Sensoris Kemplang Asap Ikan Gabus (Channa striata) dengan Penambahan Asap Cair - Herpandi Herpandi; Rinto Rinto; Indah Widiastuti; Sherly Ridhowati; Wulandari Wulandari; Puspa Ayu Pitayati; Eklin Meinatsya Putri (Universitas Sriwijaya, 2020)
Crackers is a product made through a roasting process. This study aims to determine the effect of the addition of liquid smoke on the physical and sensory characteristics of snakehead fish crackers (Channa striata). This research method used a randomized block design (RBD) with one treatment factor and was carried out with 3 replications. The treatment used was the difference in the concentration of liquid smoke (0%, 2.5%, 5%, and 7.5%). The stages of this research include physical analysis (crispness) and sensory analysis (appearance, aroma, taste, and texture). The results showed that the treatment of different concentrations of liquid smoke had no significant effect on crispness (525.67 gf-580.67 gf). The results of sensory analysis showed that the treatment of different concentrations had a significant effect on appearance, aroma and taste, but had no significant effect on the texture of kemplang. The best treatment of this research is the A1 treatment with a liquid smoke concentration of 2.5%.